Sustainability in Quantum Optics: Future Research in Renewable Energy - Amina Intes; Uwe Barroso; Wolnough Cale (Yayasan Adra Karima Hubbi, 2024)
Quantum optics is a field that has shown great potential in developing renewable energy technology. The interaction between light and matter on the quantum scale opens up opportunities for higher energy efficiency and more sustainable energy sources. However, further research is needed to integrate the principles of quantum optics into technologies that can be widely applied in the renewable energy sector. This research explores how quantum optics-based technologies can be developed and integrated into renewable energy applications to increase efficiency and sustainability. This research seeks to identify and test various approaches in quantum optics that can improve renewable energy generation and storage methods. The methods used include laboratory experiments and computer simulations to test the effectiveness of various quantum optical configurations in enhancing the energy conversion process. A multi-disciplinary approach with collaboration between physicists, engineers, and materials experts is used to achieve a deeper understanding of the potential of this technology. The research results show that using quantum entanglement and non-linear phenomena in quantum optics can significantly improve the efficiency of solar energy collection and conversion. This technique has succeeded in increasing the conversion efficiency of solar cells from conventional models by 10 to 15 percent in laboratory conditions. The conclusions of this study confirm that quantum optics have significant potential to improve sustainability and efficiency in renewable energy technologies. With further research and development, quantum optics-based technologies could contribute to global efforts to reduce dependence on fossil fuels and tackle climate change. Thus, integrating quantum optical principles into renewable energy systems should be a significant focus in future research